(3YLGFH GdCchGf aj PcQ GdHYV ef CLRGA dbeGfs - (3GHf dbeGf , dbeGf GdMcje (B- (3EHQGgje Hf dbeGf Hf CMeO Hf eMeO GdTjHGfj, CHh GdYHGS,J (B693 (3g` s
(3ChdgG (B:s
(3gPG YLGFH GdCchGf aj PcQ GdHYV ef GLRGA dbeGf GdMcje cMd GdHGJjbhf , hgh CfaY GdCcMGd ebhi GdHUQ , hfGaY GdQeO hddOeYI hGdHjGV hEf cGf YJjb hddMcI hGdZTGhI hZdX GdCLaGf s
(3BNQgG (B:s
(3Ecdjd SfHdI , ef cd NeSI OQGge Cajhf RfLHjd ef cd KdGKI OQGge s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B58s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B155 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs